A cross-sectional study of contact allergens in feminine hygiene wipes: a possible cause of vulvar contact dermatitis. Issue 4 (28th November 2022) - Newton, Jazmin; Richardson, Sophie; van Oosbre, Annika M.; Yu, Jiade; Silence, Channi
Abstract : Background: Feminine hygiene wipes marketed toward women for maintaining freshness and cleanliness of the vulva and perineum are abundant both in-store and online. Many of these products boast being "fragrance free, " "gentle, " and "for sensitive skin, " which is attractive to consumers. However, these claims do not necessarily mean they are free of potential allergens. Objective: The present study aims to investigate the presence and prevalence of potential allergens in the most used feminine hygiene wipes. Methods: An internet-based search was performed to identify best-selling name brand and generic feminine hygiene wipes. Each unique wipe was analyzed and compared to the North American Contact Dermatitis Group 80 allergens. Results: We found contact allergens are frequently present in feminine hygiene wipes, most commonly fragrances, other scented botanicals in the form of essences, oils, and fruit juices, and vitamin E (tocopherol). All wipes analyzed in this study contained potential allergens. Limitations: The inability to eliminate commercial names from analysis could have introduced bias. Conclusions: Vaginal and vulvar epithelia are highly susceptible to contact allergens, often found in products marketed for feminine hygiene and cleanliness. Providers should caution patients against trusting product labeling claims to avoid incidental contact allergy and encourage simply cleansing the vulva with water.